Pengaruh Konsentrasi Natrium Bikarbonat dalam Pasta Gigi Terhadap Streptococcus mutans - Nisaa, Khairun; Widjijono, Widjijono (Universitas Muhammadiyah Yogyakarta, 2008)
Antimicrobial substance into dentifrice is to destroy or inhibit the microorganisms that are associated with oral disease. One of the antimicrobial substances is a sodium bicarbonate. Sodium bicarbonate characterized as antimicrobial agent and buffering solution, the function of a buffer is to stand with change in pH after additional acid or base. This research is carried out to ï¬nd out the effect of sodium bicarbonate concentration dentifrice to the growth of Streptococcus mutans. This research is an experimental laboratory. One millimeter suspension of Streptococcus mutans inoculated in MHA. After wards the agar was divided into 5 sectors and each was made a well and each well was loaded sodium bicarbonate dentifrice with 5 %, 10%, 15%, 20% concentration. The media was incubated for 48 hours in 37Â°C. Potential antimicrobial was measured by sliding caliper with 0. 01 mm in accuracy. This research uses twenty ï¬ve samples. Data analysis was done One-way ANOVA to know the effect variance concentration, and LSDM5 to know mean difference between groups sodium bicarbonate. The result of this research showed that there were significant difference among the concentration sodium bicarbonate within dentifrice to the growth Streptococcus mutans @2 0.05). The result of LSDâ€ 05 showed that there were significant differences between 0% concentration of sodium bicarbonate within dentifrice of 5%, 10%, 15%, and 20%. The conclusion of this research was that effect of sodium bicarbonate concentration within dentifrice to the growth of Streptococcus mutans.